Anti-inflammatory effects of inosine in allergic lung inflammation in mice: evidence for the participation of adenosine A(2A) and A(3) receptors - da Rocha Lapa, Fernanda (Springer Netherlands, 2013)
Inosine, a naturally occurring purine formed from the breakdown of adenosine, is associated with immunoregulatory effects. Evidence shows that inosine modulates lung inflammation and regulates cytokine generation. However, its role in controlling allergen-induced lung inflammation has yet to be identified. In this study, we aimed to investigate the role of inosine and adenosine receptors in a murine model of lung allergy induced by ovalbumin (OVA). Intraperitoneal administration of inosine (0.001–10 mg/kg, 30 min before OVA challenge) significantly reduced the number of leukocytes, macrophages, lymphocytes and eosinophils recovered in the bronchoalveolar lavage fluid of sensitized mice compared with controls. Interestingly, our results showed that pre-treatment with the selective A(2A) receptor antagonist (ZM241385), but not with the selective A(2B) receptor antagonist (alloxazine), reduced the inhibitory effects of inosine against macrophage count, suggesting that A(2A) receptors mediate monocyte recruitment into the lungs. In addition, the pre-treatment of mice with selective A(3) antagonist (MRS3777) also prevented inosine effects against macrophages, lymphocytes and eosinophils. Histological analysis confirmed the effects of inosine and A(2A) adenosine receptors on cell recruitment and demonstrated that the treatment with ZM241385 and alloxazine reverted inosine effects against mast cell migration into the lungs. Accordingly, the treatment with inosine reduced lung elastance, an effect related to A(2) receptors. Moreover, inosine reduced the levels of Th(2)-cytokines, interleukin-4 and interleukin-5, an effect that was not reversed by A(2A) or A(2B) selective antagonists. Our data show that inosine acting on A(2A) or A(3) adenosine receptors can regulate OVA-induced allergic lung inflammation and also implicate inosine as an endogenous modulator of inflammatory processes observed in the lungs of asthmatic patients.